2016
DOI: 10.1159/000452762
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Assessment Battery as a Useful Tool to Differentiate Mild Cognitive Impairment due to Subcortical Ischemic Vascular Disease from Alzheimer Disease

Abstract: Background: Prominent executive dysfunction can differentiate vascular dementia from Alzheimer disease (AD). However, it is unclear whether the Frontal Assessment Battery (FAB) screening tool can differentiate subcortical ischemic vascular disease (SIVD) from AD at the pre-dementia stage. In addition, the neural correlates of FAB performance have yet to be clarified. Methods: Patients with mild cognitive impairment (MCI) due to SIVD (MCI-V), MCI due to AD (MCI-A), and demographically matched controls completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…All the studies were conducted in an outpatient setting, where subjects were recruited by convenience or consecutive sampling from those attending geriatric medicine or neurology‐based memory clinics and dedicated referral centres (eg, a National CADASIL clinic), with additional participants including controls obtained from general practice or other community settings such as volunteer groups. Most studies were conducted in Europe (seven studies), with five in Asia, two in North America, and one in South America …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the studies were conducted in an outpatient setting, where subjects were recruited by convenience or consecutive sampling from those attending geriatric medicine or neurology‐based memory clinics and dedicated referral centres (eg, a National CADASIL clinic), with additional participants including controls obtained from general practice or other community settings such as volunteer groups. Most studies were conducted in Europe (seven studies), with five in Asia, two in North America, and one in South America …”
Section: Resultsmentioning
confidence: 99%
“…The most commonly studied single‐item instrument was the CDT ( n = 5) with six different scoring systems reported: the Rouleau, Cahn, Babins and the AD Cooperative Study scoring methods, and two versions of the CLOX, ie, CLOX1 (free drawing) and CLOX2 (copying); the CDT was also combined with the MMSE and the CLOX was combined with the Cube Copying Test . Other individual instruments included the TMT (types A and B) (n = 1), tests of delayed recall (n = 3), including the Delayed Memory Index (DMI) subtest from the Repeatable Battery for the Assessment of Neuropsychological Status Update (RBANS), and four tests of verbal fluency: the F‐A‐S Phonemic (letter) Fluency (n = 1), Categorical Fluency (n = 1), the combination of the Controlled Oral Word Association Test (COWAT) and the Rey Auditory Verbal Learning Test (RAVLT) (n = 1), and the Orthographical fluency subtest from the Taiwanese version of the FAB (n = 1) . The longest administration time was for the ACE‐R at 15 minutes and CAB at 20 minutes …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Executive function involves manipulation and update of incoming stimuli through working memory [39], and governs tasks that are conducted in a proper sequence by sustaining attention and monitoring feedback [40]. Previous studies have suggested that patients with vascular dementia/SIVD have worse executive function than those with AD [19,41], and that such discernible changes may even be identified during the very early stage [42]. Other studies have suggested that patients with SIVD have greater deficits in working memory and visuomotor speed compared to patients with AD [43].…”
Section: Discussionmentioning
confidence: 99%
“…In a study operationalizing MCI criteria, non-amnestic single-domain MCI was unexpectedly common and the authors concluded that it may represent a previously unrecognized MCI subtype associated with SSVD [ 108 ]. The Frontal Assessment Battery is a useful tool to differentiate MCI due to SSVD from AD [ 111 ]. The Montreal Cognitive Assessment performed better than the Mini-Mental State Examination to detect MCI-SSVD [ 112 ].…”
Section: Symptoms Pattern and Clinical Presentationmentioning
confidence: 99%